Stanley Martin Sapon, A study of the development of the interrogative in Spanish from the twelfth through the fifteenth centuries. Columbus, Ohio, 1951. 99 págs. - Boyd-Bowman, Peter (El Colegio de México, 2007)
Se reseñó el libro: A study of the development of the interrogative in Spanish from the twelfth through the fifteenth centuries.